A Coordinated Population Health Approach to Diabetes Education in Primary Care. Issue 6 (December 2019) - Zupa, Margaret F.; Arena, Vincent C.; Johnson, Patricia A.; Thearle, Margaret B.; Siminerio, Linda M.
Purpose: The purpose of this feasibility study was to determine the effectiveness of an insurer-based diabetes educator (DE)–driven intervention that relies on systematic restructuring of primary care (PC) linking DE services through population health, practice redesign, and coordinated care for patients with diabetes mellitus (DM) identified as high risk. Methods: Two DEs were introduced as members of PC teams and worked with practice-based care managers (PBCMs) to identify and refer DM patients considered at high risk, A1C >9%, DM-related emergency room visit or hospitalization, or reported barriers to care. Elements shown to ensure quality, including population management, diabetes self-management education and support (DSMES), and coordinated patient-centered team-based PC, were central to intervention. A1C, low-density lipoprotein (LDL), and body mass index (BMI) were collected at baseline and outcomes were followed at 3, 6, 9, and 12 months after intervention. Results: For patients who received intervention, A1C decreased on average 1.2% (95% confidence interval [CI], 0.8-1.5) from 9.6% (81 mmol/mol) to 8.4% (68 mmol/mol) over 6 months and by 1.1% (95% CI, 0.7-1.5) from 9.2% (77 mmol/mol) to 8.1% (65 mmol/mol) over 12 months, indicating durable improvement in glycemic control. There was no significant change in BMI, and LDL improvement observed at 9 months was lost by 12-month follow-up. Conclusion: Findings support the feasibility of a DE-driven intervention for patients with DM at high risk through a coordinated PC approach that improves glycemic control. The feasibility and clinical outcome of this model warrant consideration of a fresh role for DEs in the complex environment of value-based care.